Is reconstruction of composite defects of nose and cheek following tumor excision utilizing subunit principle the best? - Arora, Viresh; Ashfaq, Faisal; Rafique, Atif (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Composite defects of nose and cheek are best stage reconstructed with separate nose and cheek flaps to recreate a blended nose-cheek junction, achieved by cheek advancement flap for cheek and forehead flap or local grafts for the nasal defect. This article analyses whether reconstruction of defects utilizing well-known subunit principle is cosmetically the best? Methods: Case records of fifteen patients of nasal cancers extension into the cheek from January 2011 to December 2015 were analyzed retrospectively. Results: Out of fifteen patients 8 were men and 7 women, two patients had squamous cell carcinoma, rest had basal cell carcinoma. Average size of defect was 4.5 cm. Modified Imre’s cheek advancement flaps was used in all to reconstruct cheek defects while paramedian forehead flap was used for nasal reconstruction in 13 patients, skin graft and nasal advancement flap in one each. Eight patients underwent single stage reconstruction while seven with full thickness nasal defects had a delayed reconstruction. 13 patients rated their final appearance as satisfactory, while surgeon rated 12 patients with well-blended nose-cheek junction as satisfactory and lateral migration of junction being unsatisfactory. Alar retraction was observed in two patients with full thickness nasal defects. Two patients who underwent inner nasal lining reconstruction developed wound dehiscence while simultaneous reconstruction of nose and cheek was performed. Conclusions: Subunit principle application for composite nose and cheek results in symmetrical nose-cheek junction and appears excellent technique in achieving a satisfactory aesthetic outcome. Optimal results in full thickness nasal defects are achieved where reconstructing is delayed.